Convicted - Romig, Aleatha ([United States] : Aleatha Romig, 2013)
There were still lessons to learn and consequences for the truth! Over time, the role of teacher changed, and domination turned to desire. Claire and Tony found their way back to one another, but just when they seemed to have it all the game master exposed the truth. Is her new prison-- a tropical island-- truly less lonely than the prison cell she had inhabited? Can Tony forgive her for leaving him-- again? Sins of the past and truths are revealed as the game master deals from a stacked deck....
Keywords: Erotic stories; Psychological fiction